2017
DOI: 10.1111/acfi.12318
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student engagement in large management accounting lectures

Abstract: The education literature suggests a student‐focused teaching strategy to improve students’ engagement in a lecture. However, in traditional accounting lectures students take the role of passive and anonymous recipients of knowledge. This paper reports on two cycles of an action research project, developing and refining a blended learning model, with the purpose of enhancing students’ engagement in the lectures of a large management accounting course. Results of our study find that engagement was enhanced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 56 publications
(180 reference statements)
0
26
0
2
Order By: Relevance
“…To date, there is little research into the application of HyFlex to large classes where student engagement is a challenging pedagogical issue (Frick, Birt, & Waters, 2020). Furthermore, a recent review on student engagement (Bond, Buntins, Bedenlier, Zawachi-Richter, & Kerres, 2020) concluded that more research is needed to shed light on how the learning environment affects student engagement.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is little research into the application of HyFlex to large classes where student engagement is a challenging pedagogical issue (Frick, Birt, & Waters, 2020). Furthermore, a recent review on student engagement (Bond, Buntins, Bedenlier, Zawachi-Richter, & Kerres, 2020) concluded that more research is needed to shed light on how the learning environment affects student engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Although students may have different preferences for learning, it appears that combining the visual method of learning and graphical content may improve students' learning performance. This was also highlighted by Frick et al (2020) who noted that in traditional accounting courses, students take on the role of passive and anonymous recipients of knowledge. Thus, it was suggested that using online learning materials and systems, as in the context of blended learning, could enhance students' engagement and concentration.…”
Section: Application Of Online Component Of Blended Learning Among Accounting Studentsmentioning
confidence: 93%
“…[10] The successful outcomes as a result of the implementation of such models in large introductory classes in higher education are well documented. [11,12] Seery has comprehensively reviewed flipped teaching in chemistry higher education and charted its evolution from teacher's intuition to an evidence-supported practice set within a theoretical framework of cognitive load theory and self-determination. [13] Eichler & Peeples carried out a comparison of the effects of 'flipped' and 'non-flipped' approaches to teaching general Chemistry courses.…”
Section: The Foundation Yearmentioning
confidence: 99%